Regulatory T-cells and GARP expression are decreased in exercise-associated chikungunya viral arthritis flares - Dobbs, John E.; Tritsch, Sarah R.; Encinales, Liliana; Cadena, Andres; Suchowiecki, Karol; Simon, Gary; Mores, Christopher; Insignares, Silvana; Orozco, Vierys Patricia Villamil; Ospino, Mirna; Echavez, Lil Avendano; Gomez, Carlos Andres Herrera; et al. (Frontiers in Immunology, 2022)
Objective: Chikungunya virus (CHIKV) causes persistent arthritis, and our prior study showed that approximately one third of CHIKV arthritis patients had exacerbated arthritis associated with exercise. The underlying mechanism of exercise-associated chikungunya arthritis flare (EACAF) is unknown, and this analysis aimed to examine the regulatory T-cell immune response related to CHIKV arthritis flares. Methods: In our study, 124 Colombian patients with a his¬tory of CHIKV infection four years prior were enrolled and 113 cases with serologically confirmed CHIKV IgG were used in this analysis. Patient information was gathered via questionnaires, and blood samples were taken to identify total live peripheral blood mononuclear cells, CD4+ cells, T regulatory cells, and their immune markers. We compared outcomes in CHIKV patients with (n = 38) vs. without (n = 75) EACAF using t-tests to assess means and the Fisher’s exact test, chi-squared to evaluate categorical variables, and Kruskal-Wallis tests in the setting of skewed distributions (SAS 9.3). Results: 33.6% of CHIKV cases reported worsening arthritis with exercise. EACAF patients reported higher global assessments of arthritis disease ranging from 0-100 (71.2±19.7 vs. 59.9±28.0, p=0.03). EACAF patients had lower ratios of T regulatory (Treg)/CD4+ T-cells (1.95±0.73 vs. 2.4±1.29, p = 0.04) and lower percentage of GARP (glycoprotein-A repetitions predominant) expression per Treg (0.13 ± 0.0.33 vs. 0.16±0.24 p= 0.020). Conclusion: These findings suggest relative decreases in GARP expression may indicate a decreased level of immune suppression. Treg populations in patients with CHIKV arthritis may contribute to arthritis flares during exercise, though current research is conflicting.